EN-06 ion exchange brine management - Chia, David Kok Hee (Nanyang Technological University, 2021)
Disinfection by-products (DBPs) are commonly formed when the disinfectant chemical such as chlorine reacts with the natural organic matter (NOM) in surface water. The removal of NOM was found effective in reducing the DBPs formation. As such, many treatment approaches in reducing NOM in the feed water has emerged. Magnetic ion-exchange (MIEX®) resin has been extensively studied and was found effective in removing NOM in surface water. MIEX resin can be regenerated with the use of NaCl brine. However, the regeneration of spent MIEX produces waste brine with high concentrations of organics and salts, which is the major drawback for MIEX process. One approach to reduce the volume of disposal of waste brine is through treat and reusing the waste brine using nanofiltration (NF) technology. Nanofiltration (NF) membranes can be used to filter organics and divalent ions whilst allowing NaCl brine to pass through to regenerate brine for regeneration of spent MIEX. In this study, organics and salt removal of 3 commercial NF membranes were evaluated using bench scale crossflow NF filtration system. NFX was found to have the highest organics rejection rate of greater than 99% and divalent ions removal of approximately 90%. Therefore, NFX was chosen as the most suitable membrane to undergo regeneration of the membrane for multiple cycles of recovery of waste brine to minimise waste products produced in the regeneration stage, thus, closing the loop in recovery of waste brine. From the experiment of multi-cycle membrane regeneration, NFX portrays high possibility of enabling the entire process to have minimal wastage produced as treatment by-products.